Potensi Clitoria ternatea sebagai Upaya Terapi Preventif Penyakit Alzheimer : Kajian Literatur: Potensi Clitoria ternatea sebagai Upaya Terapi Preventif Penyakit Alzheimer - Lina Kurniasari; N. P. Ayu Wulandari Dewi (Jurnal Jejaring Matematika dan Sains, 2022)
One of degenerative disease on elderly people is dementia. Dementia is characterized by memory loss. Antioxidant is one of the pharmacological therapies that use to treat Alzheimer’s disease. Clitoria ternatea is one of plant that contains antioxidant. The purpose of writing this article is to provide information about the benefits of Clitoria ternatea in curing and preventing alzheimer’s disease. This method is carried out by studying literature from several related journals. The result showed that Clitoria ternatea is proven to be able to treat and prevent Alzheimer’s disease